Difficult diagnosis and surgical treatment of acute aortic syndrome - Kurpińska-Kac, Wioleta; Osowski, Jakub; Sobczyk, Natalia; Łoś, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2021)
Acute aortic syndrome (AAS) continues to be a major clinical problem due to the need for urgent diagnosis and complex surgical management. We present a case that was not only surgically demanding, but also caused many difficulties in the preoperative diagnostic process. Typical clinical symptoms of AAS did not correlate with imaging study results, including computed tomography (CT) angiography and transthoracic echocardiography (TTE). A 64-year-old female patient was admitted to the hospital due to tearing, excruciating chest pain lasting for 18 hours and radiating to the interscapular area. Pain tended to slightly decrease with time. Other symptoms were transient numbness of the left lower extremity (a few hours) and amblyopia, lasting for several minutes. She had a history of poorly controlled hypertension, nicotinism, nephrectomy due to renal cell carcinoma, peptic ulcer disease, anxiety, depressive disorder, and addiction to clonazepam.